Bibliometric Analysis of Mushroom Poisoning: From Diversity to Clinical Management - Jason Kar Seng, Tang; Chia Wei, Phan; Yee Shin, Tan; Vikineswary, Sabaratnam; Jaya Seelan Sathiya, Seelan; Mohamad Hasnul, Bolhassan (Begell House, 2022)
The earliest publication related to mushroom poisoning dates back to 1837. To date, bibliometric analysis related to the field of mushroom poisoning has not been published. This study aimed to assess the most significant publications in this field as well as the associated trends and important drivers in the research related to mushroom poisoning. The Scopus database was screened to identify relevant publications on mushroom poisoning. A total of 985 publications with a minimum of five citations were identified and analyzed. Pearson’s correlation demonstrated an insignificant weak negative correlation (Pearson’s correlation of −0.020, P > 0.01) between the number of years since publication and the number of citation counts of a paper. Bradford’s law of scattering revealed that one-third of publications were published in 31 core journals, with Clinical Toxicology topping the list (41 papers). VOSviewer was used to generate a network visualization based on country. The United States was the largest contributor of publications on mushroom poisoning, contributing 19.6% of 985. China is an emerging leader in publications on mushroom poisoning research since 2011, with the most recent average publication year of 2011.18. A term map was also created to visualize the co-occurrence of key terms, whereby Amanita phalloides–related research appeared to be the most frequently published topic in this field. In conclusion, the results of this bibliometric study shed light on the status of mushroom poisoning research and can guide investigators on current research trends for high-impact knowledge contribution in the field.